Atomistic modelling of friction of Cu and Au nanoparticles adsorbed on graphene - Khomenko, A.V.; Prodanov, N.V.; Persson, B.N.J. (Condensed Matter Physics, 2013)
We present classical molecular dynamics calculations of the behavior of copper and gold nanoparticles on a graphene sheet, sheared with a constant applied force Fa. The force Fs acting on the particle from the substrate depends on the material of the nanoparticles (Au or Cu), and exhibits a sawtooth dependency on time, which we attribute to local commensurability between the metal nanoparticle surface atomic positions with the graphene lattice. The time-averaged value of Fs (the friction force) acting on Au nanoparticles increases linearly with the contact area, having slopes close to the experimentally observable ones. A qualitative model is proposed to explain the observed results.